Solve Using the Square Root Property 2x^2+3x-20=0

Math
2×2+3x-20=0
Factor by grouping.
Tap for more steps…
For a polynomial of the form ax2+bx+c, rewrite the middle term as a sum of two terms whose product is a⋅c=2⋅-20=-40 and whose sum is b=3.
Tap for more steps…
Factor 3 out of 3x.
2×2+3(x)-20=0
Rewrite 3 as -5 plus 8
2×2+(-5+8)x-20=0
Apply the distributive property.
2×2-5x+8x-20=0
2×2-5x+8x-20=0
Factor out the greatest common factor from each group.
Tap for more steps…
Group the first two terms and the last two terms.
(2×2-5x)+8x-20=0
Factor out the greatest common factor (GCF) from each group.
x(2x-5)+4(2x-5)=0
x(2x-5)+4(2x-5)=0
Factor the polynomial by factoring out the greatest common factor, 2x-5.
(2x-5)(x+4)=0
(2x-5)(x+4)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
2x-5=0
x+4=0
Set the first factor equal to 0 and solve.
Tap for more steps…
Set the first factor equal to 0.
2x-5=0
Add 5 to both sides of the equation.
2x=5
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2x=5 by 2.
2×2=52
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2×2=52
Divide x by 1.
x=52
x=52
x=52
x=52
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
x+4=0
Subtract 4 from both sides of the equation.
x=-4
x=-4
The final solution is all the values that make (2x-5)(x+4)=0 true.
x=52,-4
Solve Using the Square Root Property 2x^2+3x-20=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top